Exponential Growth Pattern of Consumer Well-Being and Attractiveness of Tourism Digital Destination - Albert Hasudungan; Eka Ardianto; Redha Widarsyah (Journal of Economics, Business & Accountancy, 2021)
The study aims to explore connective patterns of seven dimensions of tourism consumer well-being, namely environmen-tal altruism, spiritual attunement, inspirational mindfulness, bio-psychological aspect, entrepreneurship, social connectedness, and cultural identity, to induce more tourism growth attractiveness in visiting the digital destination of the My Trip My Adventure (MTMA) Labuan Bajo YouTube platform. The study stems from a postmodern approach where the virtual world and reality are eroded in digital technology development. This study enriches the postmodern perspective by elaborating on seven dimensions of tourism consumer welfare and the 4 V’s of digital technology innovation (volume, variety, velocity, and veracity). This study collected comments, replies, and like expressions on YouTube from October 2016 to October 2019 from MTMA Labuan Bajo. Then, researchers conducted thematic analysis and social network analysis. This research confirms polynomial growth pattern from the seven tourism consumer well-being dimensions. Generally, the pattern goes up from environmental well-being to inspirational mindfulness. Then, it descends to biophys-ical well-being. Due to having exponential growth; tourism needs to be absent temporarily. After that, the growth goes up on social and cultural well-being. The findings can benefit tourism practitioners in orchestrating seven dimensions of tourism consumer well-being as destination orchestrators.